Religious Character Habituation Through School Culture in Elementary Schools: Pembentukan Karakter Religi Melalui Budaya Sekolah di Sekolah Dasar - Ghozi, Pramudya Al; Amrullah, Muhlasin (Universitas Muhammadiyah Sidoarjo, 2025)
Background : Character education has long been recognized as a key foundation in preparing young generations to face social and moral challenges. Specific Background: In the Indonesian context, the cultivation of religious character is emphasized through daily school practices and values. Knowledge Gap: Previous studies have mostly focused on moral or civic character at the secondary level, while little attention has been given to the systematic habituation of religious character in elementary schools. Aims: This study aims to describe the habituation of religious character through school culture at SDN Curahmalang 1 and to identify its supporting and inhibiting factors. Results: Using a qualitative descriptive approach with observation, interviews, and documentation, the study reveals that religious practices such as 5S (smile, greeting, courtesy, respect), daily prayers, gratitude, tolerance, and congregational worship foster students’ religiosity, responsibility, and moral values. Supporting factors include teachers’ roles, parental involvement, and conducive school environments, while limited facilities remain a challenge. Novelty: This research highlights a comprehensive framework for embedding religious character within the culture of elementary schools. Implications: The findings suggest that a collaborative and structured school culture can significantly contribute to holistic character development in early education. Highlights: Daily habituation strengthens students’ religious character. Teachers and parents play a vital collaborative role. School culture provides a sustainable framework for value formation. Keywords: School Culture, Character Education, Religious Values, Elementary School, Habituation